MANAGEMENT OF NECK FEMUR FRACTURE IN ADULT BY MINI-DHS AND BIPLANE DOUBLE SUPPORTED SCREW FIXATION TECHNIQUE - PACHORI, SACHIN; SINGH, PRATAP; KUMAR, MOHIT; CHOUDHARY, LAXMAN (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The aim of the study was to study the management of neck femur fracture in adult by mini-DHS and BDSF technique; an innovative procedure. Methods: This study was conducted on 20 Patients with neck of femur fractures, who underwent mini DHS with 6.5 mm cc screw with biplane double supported screw fixation technique in the Department of Orthopaedics, Government Medical College and Associated Groups of Hospitals, Kota during year 2019–2021. Results: Out of 20 cases, 14 are male and six are female and age-wise distribution <20 years, one patient 20–40 years, 11 patients and >40 years, eight patients. Mode of injury mainly road traffic accident, Average Harris hip score 91.35, 15 patients (75%) achieved excellent result, radiologically fracture union was seen in 19 patients (95%). Conclusion: Although anatomical reduction is crucial, Mini DHS with 6.5 mm cc screw with BDSF-method ensures reliable fixation, early rehabilitation, and good functional outcome especially in adult.